Cold hard truth on men, women & money : 50 common money mistakes and how to fix them - O'Leary, Kevin, 1954- (New York : Gallery Books, 2013)
From bestselling author and television superstar Kevin O'Leary comes a new financial guide that takes you through money mistakes at every stage of life and teaches you how to avoid them. Don't spend too much. Mostly save. Always invest. This is simple advice, but it's often the simple advice that's easy to swallow and hard to follow. Kevin O'Leary understands that getting a handle on your personal finances can be challenging at any age. Whether you're a parent struggling to explain savings to your children, a student contemplating a big loan to pay for school, a newly engaged couple considering joint bank accounts, or a baby boomer entering retirement, Kevin offers solid, practical advice to help you make and keep more money. As a lead shark on ABC's Shark Tank, Kevin's success with money management and in business is legendary. But he's made mistakes along the way, too, and he's written this book so others can benefit from his experiences and learn how to avoid debt, how to save money, and how to invest for a brighter future. Each chapter is geared to a specific age or stage in life and looks closely at your relationship with money and how simple changes in thinking and decision-making can result in more cold hard cash in your wallet or bank account. You'll find real-life examples of common money mistakes and strategies for avoiding them, "Cold Hard Truth" quizzes and charts aimed at boosting your financial wisdom, and tips and tricks for making more money and growing it faster to achieve financial freedom. - Publisher.
The star of ABC's "Shark Tank" offers foolproof financial advice that will guide you through life's financial milestones so you can invest, spend, and save the smart way--no matter how old you are or how much you earn.
Introduction: Money problems are financial opportunities -- Part one: Spend less, save well, invest often. Money lessons I learned from my mother : spending, saving, investing: a personal-finance quiz -- Your 90-day number : cold hard truth card -- Save your money, save your life : reviving ghost money -- Invest right, invest now : 5 investment rules to live by -- Debt-free first : money pledge -- Part two: Youth and money: learning & earning, dating & mating. Kids and cash : test your child's money smarts -- The high cost of higher education : quiz: are you ready for the high cost of Higher Ed? -- Boomers and boomerangs: when generations financially collide : 10 steps for getting your kids out of your basement -- Young love and money : 10 financial questions to ask your partner before you move in together -- Part three. Marriage, mortgage, and children. Marriage and money : get hitched and stay rich: 10 ways to minimize wedding-spending madness -- House poor, house rich : 10 ways to renovate smarter -- Cash in the cradle : 5 ways to minimize baby-spending madness -- Avoiding money pits : 4 more money pits to avoid -- Part four: Midlife money matters & your financial legacy. Midlife and money karma : measure your midlife money karma -- Divorce, remarriage, and gold diggers : how to spot a gold digger -- Debt, divesting, and downsizing : 10 crucial financial questions you must ask about late-in-life care -- Epilogue: Getting to "enough."
"Originally published in 2012 in Canada by Doubleday Canada"--Title page verso.
Keywords: Finance, Personal; Finance, Personal; Personal finance; Nonfiction